On the occurrence of wet and dry spells in Bihar - CHOWDHURY, A. (MAUSAM, 1981)
Probability concept has been adopted to demonstrate the importance of dry and wet spells for planning weather sensitive agricultural operations: Daily rainfall data from 1 June to 31 October for the period 1936 to 1969 for six stations ill Bihar have been analysed. Each month has been divided into three 10 or 11 day periods as the case may be, Basic and transitional probabilities of a dry or wet day, depending upon the state of weather on the previous day(s) have been determined and discussed.